TINDAK KEKERASAN TERHADAP PEREMPUAN DALAM RUMAH TANGGA (STUDI KASUS DI DESA PUSIAN KECAMATAN DUMOGA KABUPATEN BOLAANG MONGONDOW) - Wowor, Indah Maissy; Matheosz, Jenny Nelly; Mamosey, Welly E. (Universitas Sam Ratulangi, 2020)
Marriage is a fundamental necessity run by a man and a woman to legally have a relationship as a married couple. By getting married, a commitment in a relationship will awaken strongly to give each other confidence, compassion, and attention. Married couples expect happiness they can get from marriage. The purpose of marriage is to get happiness, the manifestation of the happiness of a married couple is by establishing a harmonious relationship in his household.Every family would ideally expect the creation of happiness and harmony in his household. But the reality is not always in line with hope again. Tensions and conflicts often arise, disagreements, debates, quarrels, mocking, or even taking the usual time, all of them should be resolved by way of deliberation. The problem in the home although it looks small and trivial but can result in the disruption of the harmony of the husband's relationship to bring about domestic violence.Violence against women in households in the village Pusian Dumoga District Bolaang Mongondow in the form of physical violence is kicking, hitting, thrown using the goods. Non-physical violence is to pronounce profanity, curb, snap and threaten. The latter is economic violence as it is rarely given a living and abandoning families. The public understanding of violent acts is considered reasonable by the informant neighbors and the community is afraid to interfere with family problems.Â Keywords: violence, women, households